A framework for the Diagnosis of Diabetic Retinopathy Using Deep Learning Techniques - Anjanadevi, V.; Hemalatha, R.; Venkateshwar, R.; Naren, J.; Vithya, G. (International Journal of Psychosocial Rehabilitation, 2024)
Diabetic retinopathy, or diabetic eye disease, is a medical condition that manifests itself in the retina of the human eye. The effects of the rudimentary stages of this disease include blurred vision, seeing dark spots due to accumulation of blood vessels, and later stages of this disease can cause complete blindness in 90% of cases. The detection and diagnosis of diabetic retinopathy is well established in the field of medicine, and it is performed by professionals only. The process is known to be expensive and cumbersome. However, the rise of machine learning and AI has paved the path towards disease detection, creating a niche for diabetic retinopathy detection. This paper presents a deep learning-based framework for the diagnosis and detection of diabetic retinopathy.